2005
DOI: 10.1038/sj.bjc.6602559
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of PTEN protein and loss of epidermal growth factor receptor gene mutation in lung cancer with natural resistance to gefitinib (IRESSA)

Abstract: Gefitinib (IRESSA), an epidermal growth factor receptor (EGFR) tyrosine kinase (TK) inhibitor, has antitumour activity in the advanced non-small-cell lung cancer (NSCLC) setting. However, in chemotherapy-naïve patients with advanced NSCLC, the addition of gefitinib to standard chemotherapy regimens failed to increase survival. These results suggest the need for improved patient selection and combination rationales for targeted therapies. We have identified subpopulations of an adenocarcinoma cell line that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 28 publications
4
86
1
Order By: Relevance
“…42 In addition, homozygous deletion of the PTEN gene was associated with the development of gefitinib resistance in lung cancer cells. 43 Interestingly, other investigators showed that irradiation restored PTEN expression in H-157 lung cancer cells with a low expression of PTEN and sensitized these cells to gefitinib in vitro. 44 Furthermore, forced expression of PTEN in prostate cancer cells by a doxycycline-inducible system sensitized these cells to gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…42 In addition, homozygous deletion of the PTEN gene was associated with the development of gefitinib resistance in lung cancer cells. 43 Interestingly, other investigators showed that irradiation restored PTEN expression in H-157 lung cancer cells with a low expression of PTEN and sensitized these cells to gefitinib in vitro. 44 Furthermore, forced expression of PTEN in prostate cancer cells by a doxycycline-inducible system sensitized these cells to gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, the general activation of the PI3K pathway (by PTEN loss or PI3K mutation) in colon cancer cell lines predicts lack of response to cetuximab (Frattini et al, 2007;Jhawer et al, 2008). A reduction in PTEN expression is also associated with gefitinib resistance (Kokubo et al, 2005). Interestingly K-Ras mutations, which are known to activate PI3K, are also associated with poor outcome after certuximab treatment (Lievre et al, 2006).…”
Section: Alterations Of the Pten Pathway Associate With Poor Responsementioning
confidence: 96%
“…Specifically, activating mutations and gene amplifications of EGFR and HER2 are found in ovarian, breast and other cancers (Kokubo et al, 2005;Moasser, 2007;Vermeij et al, 2008). Particular combinations of growth factor receptor complexes (such as HER2/HER3 and EGFR/GAB1) are able to activate PI3K in a context-dependent manner (Wallasch et al, 1995;Laffargue et al, 1999).…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…3 Similarly, it promotes resistance to EGFR tyrosine kinase inhibitors in glioblastoma, colon, and lung cancer. [4][5][6] In gastrointestinal stromal tumors (GISTs), KIT and PDGFRA are fundamental therapeutic targets; however, the majority of GIST patients eventually develop resistance to imatinib mesylate and to other receptor tyrosine kinase inhibitors currently applied in the clinic. 7 This resistance is mainly due to the re-activation of KIT signaling by the acquisition of secondary KIT mutations.…”
mentioning
confidence: 99%